Programa de ejercicios aeróbicos para mejorar la movilidad articular del adulto mayor en tiempos de pandemia, en el sector la delia Parroquia Pimocha del cantón Babahoyo, Provincia de los Ríos - Espinoza López, Karla Jamilet (2021)
The purpose of the present study was to develop an aerobic exercise program aimed at older adults in order to improve their level of joint movement capacity and thus their quality of life, since their functional capacity will also benefit. The methodology used was a qualitative study with a non-experimental design with a cross-sectional and descriptive level, techniques such as the interview and the application of the Senior Fitness Test were used in two tests, the first called Back scratch test. behind the back), whose objective was to evaluate the flexibility of the upper body and the other called Chair-sit and reach-test (Test of sitting and reaching the extended foot). The sample consisted of 15 older adults, the same ones who were research subjects. Among the results obtained, a poor assessment was reflected regarding the application of the test in the group of older adults, for which the proposal of the aerobic exercise program that improves joint mobility in this vulnerable group was chosen as a solution.